IMPLEMENTASI SISTEM PENGGAJIAN BERBASIS WEB MENGGUNAKAN METODE HYBRID - Liska sumarni; Simanjuntak, Pastima (Computer Science and Industrial Engineering, 2025)
The development of computer technology encourages companies to adopt digital systems, including payroll systems. However, the Sendanu Darul Ihsan Village Office, Riau, still uses a manual Excel-based method, which often triggers errors such as incorrect NIK input and inaccurate salary calculations. This research project aims to create a web-based payroll system using a hybrid method, namely a combination of the Waterfall method and the CodeIgniter 3 platform. This application is designed with a Model-View-Controller (MVC) approach to facilitate data handling, using Sbadmin2 bootstrap which provides a responsive, modern, and easy-to-use front end. The waterfall technique ensures that development is carried out in a structured manner through the steps of analysis, design, coding, testing, and implementation. It is hoped that this method will reduce errors, speed up the payroll process, and increase the efficiency of the village office.